Food Allergies in Modern Life - Manti, Sara; Marseglia, Gian Luigi; Leonardi, Salvatore (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Food allergy, a specific immune response that occurs reproducibly upon exposure to a food allergen, is an increasing public health problem, causing a significant burden for affected patients, resulting in dietary restrictions, fear of accidental ingestions and related risk of severe reactions, and reduced quality of life. Clinical presentation ranges from mild to life-threatening symptoms. Component-resolved diagnosis with recombinant allergens has improved the diagnosis and, consequently, clinical management. Currently, there is no specific treatment for food allergy, so the only available management is limited to strict dietary avoidance, education on prompt recognition of symptoms, and emergency treatment of adverse reaction. In parallel, novel knowledge on the pathogenesis of food allergy is opening the way to new trials investigating several allergen-specific and allergen non-specific therapies, aiming to prevent the development of food allergy and acquire a persistent food tolerance.